Taxation and Development - Bird, Richard (World Bank, Washington, DC, 2012)
For more than half a century, scholars and international agencies have been making recommendations about taxation in developing countries. The advice economists have offered to developing countries has changed over time, particularly regarding income and consumption taxes. Why? What do we know now about taxes and developing countries that we did not know 50 years ago? What do we still not know that we really should know? What should scholars and international agencies do if they wish to make tax policy recommendations that are economically sensible and likely to prove feasible, acceptable, and helpful in practice? This brief note offers some tentative answers to these complex questions.